2021
DOI: 10.1523/eneuro.0196-21.2021
|View full text |Cite
|
Sign up to set email alerts
|

Single Dose of Amphetamine Induces Delayed Subregional Attenuation of Cholinergic Interneuron Activity in the Striatum

Abstract: Single dose of amphetamine induces delayed subregional attenuation of cholinergic interneuron activity in the striatumAbbreviated title: Amphetamine-induced attenuation of ChI activity

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(5 citation statements)
references
References 64 publications
3
2
0
Order By: Relevance
“…amphetamine exposure (Ztaou et al, 2021), which is consistent with our concept that addictive substances suppress striatal CIN activity. Surprisingly, acute cocaine exposure in vivo or ex vivo has been shown to increase striatal cholinergic activity (Mark et al, 1999;Witten et al, 2010).…”
Section: Reinforcement Cognitive Flexibility and Cin Activitysupporting
confidence: 91%
See 1 more Smart Citation
“…amphetamine exposure (Ztaou et al, 2021), which is consistent with our concept that addictive substances suppress striatal CIN activity. Surprisingly, acute cocaine exposure in vivo or ex vivo has been shown to increase striatal cholinergic activity (Mark et al, 1999;Witten et al, 2010).…”
Section: Reinforcement Cognitive Flexibility and Cin Activitysupporting
confidence: 91%
“…Therefore, the reduction in DMS CIN firing is more likely to reflect changes in synaptic transmission. Interestingly, a recent study also reported a downregulation of CIN activity in the ventral striatum after acute amphetamine exposure (Ztaou et al, 2021), which is consistent with our concept that addictive substances suppress striatal CIN activity. Surprisingly, acute cocaine exposure in vivo or ex vivo has been shown to increase striatal cholinergic activity (Mark et al, 1999;Witten et al, 2010).…”
Section: Reinforcement Cognitive Flexibility and Cin Activitysupporting
confidence: 91%
“…We found that both non-contingent and contingent cocaine exposure led to a long-lasting reduction in the spontaneous firing of DMS CINs. Interestingly, recent studies have reported the downregulation of CIN activity in the ventral striatum after acute amphetamine exposure 53 , and D2R overexpression in Nac CINs after cocaine self-administration 32 , which aligns with our finding that addictive substances suppress striatal CIN activity. Surprisingly, acute cocaine exposure in vivo or ex vivo has been shown to increase striatal cholinergic activity 54 .…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, a single exposure to psychostimulant drugs such as d-amphetamine, cocaine or methylphenidate enhances motor behaviors whose manifestations depend on the dose administered (Gaytan et al, 1998;Yates et al, 2007). At low doses, these drugs stimulate fast exploratory activity characterized by an increase in locomotion and rearing (Yates et al, 2007;Ztaou et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…However, at high doses, psychostimulants promote a variety of repetitive behaviors ranging from in-place stereotypies (continuous sniffing, circling, intense grooming, and self-gnawing) to patterned locomotion and continuous up-and-down rearing motion often accompanied by intermittent episodes of wall licking (Yates et al, 2007;Ztaou et al, 2021).…”
Section: Introductionmentioning
confidence: 99%